ENT 530 Social Media Portfolio: Haurabelle.AF / Afrina Rauhah Abdul Jamil - Abdul Jamil, Afrina Rauhah (2021)
Haurabelle.AF is a dropship business account for a Haurabelle company. Haurabelle is a Muslim clothing business that has a minimal modern design for each of their clothes and is in line with the passage of time. The business sells each set of their clothes at a reasonable price which is very affordable for a set of clothes. This business has an outlet at No 72, Jalan BDS 2, Bukit Desa Semantan, 28000 Temerloh, Pahang. Customers can go to Haurabelle's own premises or buy through their website. In addition, Haurabelle is active on social media accounts such as on their company's Facebook and Instagram pages. The advantage of Haurabelle is that they often hold promotions that can attract customers. Customers are often interested in their simple but fashionable clothing design. Their clothes are also popular because they often produce baggy designs that are very popular with today's youth. Most of their clothing designs make daily life easier, for example, such as making it easier for women to cover their aurat, making it easier for women to perform ablutions and using comfortable materials to be worn by Muslim women out there. They also use the dropship method as one of the ways to increase their monthly sales. In addition, this dropship method is opened to help those who are interested to increase their side income. Every dropship that can achieve impressive sales will be rewarded by Haurabelle.